2016
DOI: 10.1038/ctg.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal Barrier Function in Health and Disease

Abstract: The gastrointestinal tract consists of an enormous surface area that is optimized to efficiently absorb nutrients, water, and electrolytes from food. At the same time, it needs to provide a tight barrier against the ingress of harmful substances, and protect against a reaction to omnipresent harmless compounds. A dysfunctional intestinal barrier is associated with various diseases and disorders. In this review, the role of intestinal permeability in common disorders such as infections with intestinal pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
533
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(553 citation statements)
references
References 187 publications
(179 reference statements)
10
533
0
10
Order By: Relevance
“…Based on these observations, the association of intestinal inflammation and gut epithelial barrier dysfunction with the HBP cohort was examined, as many studies showed increased incidence of these with butyrate depletion [39]. We measured I-FABP, LPS, and soluble form of zonulin in plasma, biomarkers for gut epithelial health [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, the association of intestinal inflammation and gut epithelial barrier dysfunction with the HBP cohort was examined, as many studies showed increased incidence of these with butyrate depletion [39]. We measured I-FABP, LPS, and soluble form of zonulin in plasma, biomarkers for gut epithelial health [40].…”
Section: Resultsmentioning
confidence: 99%
“…Damage to this barrier makes the environment less hypoxic, conducive to aerobic bacterial growth [39,48]. Microbial-derived butyrate stabilizes gut epithelial tight junction proteins, depletes oxygen, and activates/stabilizes HIF-1 in epithelial cells [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, barrier disruption can trigger the development of GI diseases such as inflammatory bowel disease (IBD), celiac disease, and colon cancer [25]. Other systemic and metabolic diseases such as type I diabetes can also be influenced by barrier changes [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aetiology of IP is poorly understood, with early research indicating that two aspects, namely pathogenic bacteria and gliadin from gluten, are responsible for triggering IP . Although, recent research suggests that the pathogenesis of IP is multifactorial and different for each individual …”
Section: Introductionmentioning
confidence: 99%
“…Correctly identifying patients at risk of IP may allow for timely testing to determine the potential severity of IP and facilitate access to appropriate treatment interventions if required. Although the full extent of untreated IP remains underexamined, there is a considerable amount of research linking the health and integrity of the intestine to chronic disease . The purpose of this review is to summarise the known risk factors for IP and identify the most significant of these risk factors.…”
Section: Introductionmentioning
confidence: 99%